Pancreatic injury following immune checkpoint inhibitors: A systematic review and meta-analysis - Zhang, Tian; Wang, Yi; Shi, Chunhui; Liu, Xiaochun; Lv, Shangbin; Wang, Xin; Li, Weihong (Frontiers in Pharmacology, 2022)
Background: Pancreatic injury (pancreatitis, amylase/lipase elevation) is a rare adverse event of immune checkpoint inhibitors (ICIs). With the high number of clinical studies on ICIs, the incidence and characteristics of associated pancreatic injury (PI) need to be reevaluated. Methods: A systematic review and meta-analysis were conducted to assess the incidence of PI in cancer patients who received ICIs in randomized controlled trials (RCTs). PubMed, Embase, the ASCO, ESMO, and AACR conference proceedings before April 1, 2022, were investigated for relevant research. Results: 50 RCTs involving 35,223 patients were included. The incidence of ICIs-PI was 2.22% (95% CI = 1.94% - 2.53%). The incidence of PI was 3.76% (95% CI = 1.84-7.67%) when combining two ICIs, which was higher than single ICI [2.25% (95% CI = 1.91-2.65%)]. The ICIs were ranked from high to low based on the PI incidence: PD-L1 inhibitors 3.01% (95% CI = 1.86-4.87%), CTLA-4 inhibitors 2.92% (95% CI = 0.99-8.65%) and PD-1 Inhibitor 2% (95% CI = 1.67-2.39%). The ICI with the highest rate of PI was pembrolizumab 7.23.% (95% CI = 1.69-30.89%). In addition, the incidence of severe ICIs-PI was 2.08% (95% CI =1.76-2.46%); and the incidence of severe PI was 2.32% (95% CI = 1.76-3.06%) when combining two ICIs, which was higher than single ICI [1.95% (95% CI = 1.58-2.41%)]. The ICIs were ranked from high to low according to the incidence of severe PI: PD-L1 inhibitors 3.1% (95% CI = 1.7 - 5.64%), CTLA-4 inhibitors 2.69% (95% CI = 0.76 - 9.49%), PD-1 inhibitors 1.80% (95% CI = 1.41 - 2.29%). Conclusion: Treatment with multiple ICIs result in a higher incidence of PI compared to single ICIs, irrespective of the grade of pancreatic injury. The incidence of PI caused by PD-L1 inhibitors is higher than that of CTLA-4 inhibitors and PD-1 Inhibitor, and Pembrolizumab has the highest rate of ICIs-PI. Although the incidence of ICIs-PI is not high, they are usually severe (≥ grade 3 events).